Health Management Practices And Workforce Performance Among Pharmacists And Health Assistants In Saudi Arabia: A Cross-Sectional Study (The Review of Diabetic Studies, 2025)
Background: Effective health management plays a crucial role in ensuring the optimal utilization of healthcare human resources, particularly pharmacists and healthcare assistants, who are essential to ensuring medication safety and service quality. Despite healthcare reforms in Saudi Arabia, there is limited empirical evidence examining how management practices influence their performance.Aim: To examine the relationship between health management practices and workforce performance among pharmacists and health assistants in Saudi Arabia.Methods: A descriptive analytical cross-sectional study was conducted using a structured questionnaire. Statistical analysis included descriptive statistics, reliability testing, correlation analysis, and multiple linear regression.Results: A total of 320 healthcare workers participated. Health management practices showed a strong positive association with workforce performance (r = 0.62, p < 0.001). Leadership, communication, and training were significant predictors of performance.Conclusion: Strengthening health management practices can significantly enhance the performance of pharmacists and health assistants, contributing to improved healthcare quality and patient safety in Saudi Arabia.